COMBINED EFFECT OF AQUEOUS EXTRACT OF CURCUMA LONGA LINN.WITH METFORMIN IN DIABETES INDUCED NEUROPTAHIC PAIN IN RATS - ADHIKARI, ROMAN; Y, JYOTHI; BORA, DEEPIKA; VEENA A, VAMSEE (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: A number of studies previously conducted have shown that the progression of severity of diabetic Neuropathy relates the increased oxidative stress due to hyperglycemia describing the probable underlying mechanism as changes in the anti-oxidant enzyme level leading to several vascular and neuronal changes. The present investigation was carried out to observe the combined effect of Aqueous Extract of Curcuma longa Linn.(Curcumin) with Metformin in delaying of Diabetes induced Neuropathic Pain in Rats. Methods: The high-fat diet treated male SD rats were induced diabetic by a single intra-peritoneal injection of Streptozocin (35mg/kg). Eddy's Hot Plate and Hot Water Tail Immersion test were the Models used to assess the Neuropathic pain. The high Fat diet treated and Diabetic Rats were treated with Metformin (500mg/kg), Curcumin (300mg/kg) and a combination of low dose of Metformin with Curcumin, followed by the oral glucose tolerance test before and after the treatment on both Normal and Diabetic Rats. After 7 weeks of treatment TBARS, SOD, Catalase and GSH levels were also estimated in the sciatic nerve homogenate of Diabetic Rats and compared with the control followed by a supporting histopathological examination of Sciatic Nerve. Results: Diabetic Rats treated with Curcuma longa Linn. and Metformin alone and in combination showed a significant improvement in control of blood glucose level and restoration of anti-oxidant enzyme levels. There was a significant improvement in the hyperalgesia (P<0.001) due to Diabetic Neuropathy and also the reaction time to the nociceptive stimuli in Neuropathic pain models was increased after the treatment. Key Words: Antioxidant, Curcumin, Diabetes, Metformin, Neuropathy, Streptozocin